Postsecondary education, neighborhood disadvantage, and crime: an examination of life course relative deprivation - Dennison, Christopher R. (Crime & delinquency, 2019)
The growing importance of a college degree for economic stability, coupled with increasing educational inequality in the United States, suggest potential criminogenic implications for downward educational mobility. Using data from the National Longitudinal Study of Adolescent to Adult Health (Add Health), this article examines the associations between intergenerational educational mobility, neighborhood disadvantage in adulthood, and crime. Drawing on the few extant studies of educational mobility and crime, as well as social comparison theory, it tests whether the consequences of downward educational mobility are moderated by neighborhood contexts. Results suggest that downward mobility is associated with increases in crime, and most strongly in more advantaged neighborhoods. The implications of these findings for future research on social mobility, education, and crime are discussed.